Design and Analysis of Crane Hook with Different Cross Sections - Sai Kumar, Trinath; ., Majeti; Riyaz, Md; V.Narayana, M; Pathri, Murali; Baburaja, Kammuluri. (International Journal of Engineering and Technology, 2018)
Load is to be transported from one location to other location with the help of heavy vehicles, the load is placed on heavy vehicles with the help of crane or forklifts or conveyer belt, crane hook which bears the entire load. The weight of the load is related to dimensions and material of the hook.Â The major part which is to be replaced as per load is crane hook, hook is subjected to pressure and bending stress. In the present work the crane hook of different cross sections is being analyzed on model of crane hook. The crane hook is modeled on the Solidworks and analysis using Ansys. From the structural analysis performed on crane hook the stress values based on the model and stress value modifications are found.Â Â